When I chat online, I feel relaxed and work better: Exploring the use of social media in the public sector workplace in Rwanda. Issue 7 (August 2017) - Nduhura, Dominique; Prieler, Michael
Abstract: This paper explores the use of social media in the public sector workplace in Rwanda, a country that encourages new media technologies in all areas, including public institutions. In particular, we investigate how public employees reconcile job-related and private uses of social media in the workplace. To answer this question, in-depth interviews were conducted both with employees and employers. Our key findings reveal that social media are increasingly playing a central role in how public institutions function, and they are used to coordinate various activities (e.g., meetings and sharing information). Although social media are often feared for their potential to distract employees from work, in our study private uses of social media were seen as compatible with work in most institutions. Even where shortcomings were noted, they were too minimal to constitute a real threat to public institutions' productivity. Highlights: Social media are increasingly playing a central role in how public institutions function. Social media, through both private and public messages, are used to coordinate various activities. Private and public uses of social media were rather seen as compatible with work in most institutions. Regulatory frameworks do not clearly provide for appropriate uses of social media in the workplace.